2022
DOI: 10.1098/rsta.2021.0199
|View full text |Cite
|
Sign up to set email alerts
|

Bagging, optimized dynamic mode decomposition for robust, stable forecasting with spatial and temporal uncertainty quantification

Abstract: Dynamic mode decomposition (DMD) provides a regression framework for adaptively learning a best-fit linear dynamics model over snapshots of temporal, or spatio-temporal, data. A variety of regression techniques have been developed for producing the linear model approximation whose solutions are exponentials in time. For spatio-temporal data, DMD provides low-rank and interpretable models in the form of dominant modal structures along with their exponential/oscillatory behaviour in time. The majority of DMD alg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This is not a concerning issue here, since we used DMD not for reduced-order modelling of the system, but as a diagnostic tool for its dynamical behaviour. The future work will include relating the temporal evolution of the modes into a nonlinear model, together with improving robustness of the presented DMD method by taking into account flow symmetries [ 20 , 21 ], or harnessing statistical properties of the flow [ 22 ]. Such a model could provide a quantitative description of nonlinear interactions accompanying the transition to MRI turbulence.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…This is not a concerning issue here, since we used DMD not for reduced-order modelling of the system, but as a diagnostic tool for its dynamical behaviour. The future work will include relating the temporal evolution of the modes into a nonlinear model, together with improving robustness of the presented DMD method by taking into account flow symmetries [ 20 , 21 ], or harnessing statistical properties of the flow [ 22 ]. Such a model could provide a quantitative description of nonlinear interactions accompanying the transition to MRI turbulence.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Currently there are several emerging methods that allow for a broader viewpoint of building models directly from noisy data, recent innovations in DMD, for instance, have shown that statistical bagging methods can greatly increase the discovery of robust, accurate and stable linear models (Askham & Kutz, 2018; Sashidhar & Kutz, 2021). This has motivated the use of ensembling and bagging for building nonlinear, parsimonious dynamic models (Fasel et al., 2022; Hirsh et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of variants for computing A (Kutz et al., 2016), with the exact DMD simply positing A = X ′ X † where † denotes the Moore‐Penrose pseudo‐inverse. However, the optimized‐DMD (Askham & Kutz, 2018) (opt‐DMD) and bagging‐optimized DMD (Sashidhar & Kutz, 2021) (BOP‐DMD) provide algorithms that provide substantial performance gains when considering noisy data. However, such improved algorithms have yet to be incorporated with control architetures.…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…The majority of classical DMD algorithms, however, are prone to bias errors from noisy measurements of the dynamics, leading to poor model fits and unstable forecasting capabilities. Sashidhar & Kutz [ 187 ] introduce an optimized DMD method, called bagging optimized dynamic mode decomposition (BOP-DMD), by using statistical bagging methods that improves the performance of DMD methods. Unlike currently available DMD algorithms, BOP-DMD provides a stable and robust model for probabilistic or Bayesian forecasting with comprehensive uncertainty quantification metrics.…”
Section: The General Content Of the Issuementioning
confidence: 99%